2001
DOI: 10.1001/archinte.161.16.2021
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Cataract in Patients Treated With Statins

Abstract: Our study provides evidence that long-term use of therapeutic statin doses does not increase the risk of developing cataract. Concomitant use of erythromycin and simvastatin may increase the cataract risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
46
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 35 publications
0
46
0
Order By: Relevance
“…However, such a method has been extensively used in several studies (22,23), and it has been validated against medical records and pill counts, suggesting that pharmacy records are closely correlated (r ϭ 0.92) with the quantity of prescribed doses consumed (24).…”
Section: Filippi and Associatesmentioning
confidence: 99%
“…However, such a method has been extensively used in several studies (22,23), and it has been validated against medical records and pill counts, suggesting that pharmacy records are closely correlated (r ϭ 0.92) with the quantity of prescribed doses consumed (24).…”
Section: Filippi and Associatesmentioning
confidence: 99%
“…Genetically based deficiencies in mevalonate kinase (2), ⌬ 8, ⌬ 7-sterol isomerase (emapomil binding protein) (3) , 3 ␤ -hydroxysterol ⌬ 7-reductase (4), and 3 ␤ -hydroxysterol ⌬ 24-reductase (5) can result in human cataracts. Pharmacological inhibition of desmosterol reductase (6) or oxidosqualene cyclase (OSC) (7,8) causes cataracts in rodents, and inhibition of HMGCoA reductase by statins can induce cataracts in rats (9) and increase the risk of cataracts in humans (10). Simvastatin was shown to cause rapid lens damage and induce the formation of cataracts in Chbb:Thom rats (9).…”
mentioning
confidence: 99%
“…Simvastatin was shown to cause rapid lens damage and induce the formation of cataracts in Chbb:Thom rats (9). Simvastatin treatment also tripled the risk of cataracts in humans who concomitantly received two or more courses of erythromycin (10). Erythromycin can block statin catabolism and greatly increase its blood levels (11).…”
mentioning
confidence: 99%
“…Although the results of clinical safety trials collec-tively show no higher risk of cataracts in statin-treated patients [as reviewed in ref. (1)], simvastatin use in one study was associated with an increased incidence of cortical cataracts after 2 years of treatment (21), and simvastatin was recently reported to increase the risk of cataracts in patients concomitantly taking erythromycin (22). Animal studies also indicated high ocular safety of statins since cataracts were seen in dogs only after 1 or more years of treatment with high doses (16) and no reports of statin cataracts in rodents had been previously reported.…”
mentioning
confidence: 99%
“…Polymorphism in one of more of the enzymes in the sterol synthesis pathway, in the numerous proteins that mediate the pleiotropic actions of the statins (52), or in the enzymes that metabolize statins could influence the ocular safety of these drugs. Schlienger et al (22) recently reported that "concomitant use of erythromycin and simvastatin may increase the risk for cataracts" in humans. Erythromycin, along with other drugs, can inhibit the cytochrome P-450 enzymes that metabolize simvastatin and increase its serum levels (53) and, thus, risk for toxicities.…”
mentioning
confidence: 99%